Financial Technology as a Strengthening Factor in Shaping Financial Behavior: Teknologi Keuangan sebagai Faktor Penguat dalam Pembentukan Perilaku Keuangan - Kusumawati, Rahayu; Ginting, Medeilia Bernike Br; Jagad, Daniel Jaya (Indonesian Journal of Innovation Studies, 2025)
Background: Financial management in the digital era has shifted significantly due to the rapid adoption of digital financial services and technologies. Specific background: Despite increased financial inclusion in Indonesia, financial literacy remains low, leading to inconsistent financial behavior across demographic groups. Knowledge gap: Previous studies have rarely examined the comprehensive moderating role of financial technology in the relationship among financial literacy, lifestyle, financial inclusion, and financial behavior within the general public. Aims: This study aims to analyze the relationship between financial literacy, lifestyle, and financial inclusion with financial behavior, and to examine how financial technology moderates these relationships. Results: Using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with 96 respondents, results indicate that financial literacy, financial technology, and lifestyle significantly shape financial behavior, while financial inclusion does not. Financial technology strengthens the relationship between financial literacy and financial inclusion with financial behavior but not with lifestyle. Novelty: The study identifies the dual moderating role of financial technology in linking literacy and inclusion to responsible financial practices. Implications: These findings emphasize the need for integrated financial education and digital literacy programs to promote smarter and more sustainable financial management in the digital economy. Highlights Financial literacy and technology jointly shape responsible financial behavior Financial inclusion alone does not ensure improved financial management Financial technology strengthens the link between knowledge and financial discipline Keywords Financial Literacy, Financial Technology, Lifestyle, Financial Inclusion, Financial Behavior